EFEKTIVITAS PERENCANAAN PEMBELAJARAN DALAM MENINGKATKAN MUTU PENDIDIKAN DI SD ISLAM TAHFIDZ QURAN AS SYAFIIYAH - Charistya Aja Khasmi; Nur Sugesti, Abid; Ira Setiawati3; Mareta Uswatun Khasanah; Febby Dwi Yustantia; Fera Aisha Syaidina (Prodi PGMI IAI Darul Ulum Kandangan, 2024)
This study aims to determine the effectiveness of lesson planning to improve the quality of education, teacher qualifications, and improve the performance of education personnel at As Syafiiyah Islamic Tahfidz Quran Elementary School in Magelang district, Indonesia. A descriptive qualitative approach was used as the research method. Data were collected using interview, observation, and documentation techniques. The collected data were then analyzed with descriptive analysis techniques. The object of this research was conducted at Tahfidz Quran As Syafiiyah Islamic Elementary School. The results showed the effectiveness of lesson planning in improving the quality of education in elementary schools. The results of observations show that teachers have carried out massive and maximum learning planning through the preparation of lesson plans, the source of learning materials has been developed through teacher competency training, the use of varied learning media, the selection of learning materials tailored to the applicable curriculum, the implementation of evaluations in each lesson, and the development of strategies outside the classroom.